A study on the environmental and health impact of hazardous substances during welding - Ass. Prof. Elisaveta Doncheva PhD., Asistent Prof. Aleksandra Krstevska MSc., Asistent Prof. Martin Petreski MSc., Ass. Prof. Nikola Avramov PhD., Ass. Prof. Jelena Djokikj PhD. (My University, 2022)
Welding is a major joining process in modern manufacturing, primarily used for the creation of metal structures and components, as well as maintenance and repair operations. Welding, in comparison to other production processes, is regarded as a hazardous procedure that can have long-term detrimental consequences for persons and the environment. It's critical to be aware of these consequences and to look into the possibility of employing environmentally friendly methods. Each welding process has distinct risks and pollutant exposures, thus choosing the proper technique for a given application with the lowest risk of hazards is critical. This article includes a technical and environmental overview of welding operations, as well as information on the major pollutants and their estimations. The effect of welding conditions, operation, and parameter optimization on the formation of key contaminants is investigated and analyzed. The purpose of this study is to raise awareness of the dangers of welding contaminants to the environment and human health. It also suggests ways to mitigate these risks and promotes the development of green welding technology
Keywords: fumes, gases, health dangers, welding processes